Criminal Law Policy in the Distribution of Assistance Funds for Corruption Causes - Sidebang, Ledyana Olipia; Lewerissa, Yanti Amelia; Saimima, Judy Marria (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Indonesia's financial income and expenditure called Fiscal are obtained from three components, namely: Tax, Non-Tax State Revenue, and Grants. However, at the time of fiscal distribution as part of state expenditure in this case aid funds experienced problems that gave rise to criminal acts of Corruption.Purposes of the Research: : Aims to analyze criminal law policies regarding misused funds and analyze criminal law policies in corruption crimes related to misused aid funds.Methods of the Research: This study uses normative juridical with legal materials used in the study are primary, secondary, and tertiary. The collection technique is carried out through literature studies in the form of books, scientific works, and other literature.Findings of the Research: The results of the study show that the criminal law policy implemented by the Indonesian government is regulated in Law Number 31 of 1999 jo. Law Number 20 of 2001 concerning the Eradication of Corruption. Not only in this law, when Covid-19 hit Indonesia, the Indonesian government issued Government Regulation in Lieu of Law Number 1 of 2020 concerning State Financial Policy and Financial System Stability for the handling of the Covid-19 Pandemic. However, in practice, corruption still occurs in the field, and at the time of the judge's decision does not receive a punishment commensurate according to the deed and is not fully in line with the criminal law policy in Indonesia to eradicate corruption.